Effect of Perceived Organizational Politics and Core Self Evaluation on Job Satisfaction - Javed, Mehwish; ., Inamul Haq; ., Milha Shabir (Information Management and Business Review, 2014)
Many studies explore the effect of perception of organizational politics on job satisfaction but a very few investigate for the factors that are salient to this relationship. Perceptions of politics have been considered to be a source of stress at workplace which has detrimental consequences on the desired outcomes. Current study aims to explore the effects of perception of organizational politics (POP) and core self-evaluation (CSE) on employee job satisfaction. The present research also examines core self-evaluation as a moderator in the relationship between perception of organizational politics and job satisfaction. With a sample size of 100 respondents drawn from the health sector of 3rd largest city of Pakistan, named Faisalabad, the current study tested the main effects of POP and CSE on job satisfaction by using a self-administered survey having a total of 30 items. For analyzing the data, SPSS was used. As hypothesized, results show that perceived organizational politics had a significant negative relationship with job satisfaction but the results for CSE were not significant. Furthermore, CSE moderated the relationship of POP and job satisfaction, such that the negative relationship between perception of organizational politics and job satisfaction was weaker when core self-evaluation was high.